Ministry of Petroleum and Mineral Resources Decree No. 139 of the Year 2022 = وزارة البترول والثروة المعدنية قرار رقم 139 لسنة 2022 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic